Generation of non‐human primate models of Alzheimer's disease. (December 2021) - Sasaguri, Hiroki; Sato, Kenya; Kumita, Wakako; Inoue, Takashi; Kurotaki, Yoko; Nagata, Kenichi; Mihira, Naomi; Sato, Kaori; Sakuma, Tetsushi; Yamamoto, Takashi; Tagami, Michihira; Manabe, Riichiroh; et al.
Abstract: Background: Alzheimer's disease (AD) is the leading cause of dementia worldwide. Despite the considerable research efforts, exact pathomechanisms still remain unknown, and no effective treatment is available. AD research field have mainly utilized mouse models for decades, but species differences between rodents and primates may constrain us from understanding the precise disease mechanisms. Method: We utilized Transcription Activator‐Like Effector Nuclease (TALEN) to delete the 3' splicing site (SS) of exon 9 of the presenilin 1‐encoding gene ( PSEN1 ) in the common marmoset ( Callithrix jacchus ), a small new world primate. Result: We successfully deleted the 3' SS of the PSEN1 gene ( PSEN1‐ ΔE9) in the marmoset embryos by microinjection of TALEN, and obtained mutant PSEN1 neonates. Sequence analysis of mRNA in these embryos and neonates confirmed skipping of exon 9 as expected, which has been reported as a pathogenic mutation causing early onset familial AD. Whole genome sequencing illustrated an inclusive absence of off‐target effects. Quantitative analysis of amyloid‐β (Aβ) in the cultured medium of primary fibroblasts revealed elevation of Aβ42/Aβ40 ratio in PSEN1‐ ΔE9 fibroblasts. WB analysis detected uncleaved full‐length PS1 protein as well as N‐ and C‐terminal fragments of PS1 protein in the PSEN1‐ ΔE9 fibroblasts. Conclusion: To our knowledge, we have successfully generated the word's first AD model of non‐human primates. These animals are expected to show early amyloid pathology in the brain and to contribute to cutting‐edge research to elucidate primate‐specific mechanism in AD. In addition, we will make the mutant animals available to researchers worldwide in the fight against AD in the future.